Sustainability - Wasieleski, David M.; Weber, James (Emerald Publishing Limited, 2020)
The Business and Society (BAS) 360 book series is an annual publication targeting cutting-edge developments in the broad business and society field, such as stakeholder management, corporate social responsibility and citizenship, business ethics, sustainability, social entrepreneurship and others. Each volume will feature a comprehensive discussion and review of the current "state" of the research and theoretical developments in a specific business and society area. Volume Four focuses on research drawn from work grounded in "Sustainability." Scholars known in this discipline contribute to a 360-degree evaluation of the theory, including cross-discipline research, empirical explorations, cross-cultural studies, literature critiques, and meta-analysis projects. Sustainability should appeal to wide range of readers - from emerging and senior business school educators researching and teaching in the business and society field to doctoral and masters level students across the business, social sciences and natural sciences seeking to learn about this multi-discipline and sustained field of management study.
Includes index.
Print version record.
Keywords: Sustainability; Social responsibility of business; Sustainable development; Business & Economics -- Development -- Sustainable Development; Economic theory & philosophy